Complete the proof that $\left(a+b\right)^2=a^2+2ab+b^2$(a+b)2=a2+2ab+b2.
$\left(a+b\right)^2$(a+b)2 | $=$= | $\left(\editable{}\right)\left(\editable{}\right)$()() |
$=$= | $a\left(\editable{}\right)+b\left(\editable{}\right)$a()+b() | |
$=$= | $\editable{}+\editable{}+\editable{}+\editable{}$+++ | |
$=$= | $\editable{}+\editable{}+\editable{}$++ |
Complete the proof that $\left(a-b\right)^2=a^2-2ab+b^2$(a−b)2=a2−2ab+b2.
$\left(8+6\right)^2=8^2+6^2$(8+6)2=82+62
Consider the following expressions.